Thermal and physical characteristics of soils in Cyprus for use in shallow geothermal energy applications - Ramos, Rute; Aresti, Lazaros; Yiannoukos, Loukas; Tsiolakis, Efthymios; Pekris, Joseph; Vieira, Ana; Florides, Georgios A.; Christodoulides, Paul (My University, 2019)
© 2019, The Joint Center on Global Change and Earth System Science of the University of Maryland and Beijing Normal University. Ground heat exchangers in conjunction with shallow geothermal energy system applications have received significant attention in the case of renewable energy. Soil thermal properties such as thermal conductivity and specific or volumetric heat capacity are important aspects for the design of such systems, affecting the performance. They can be obtained with the use of empirical prediction models, laboratory tests and/or in situ tests. Laboratory tests can be performed either under steady-state or under transient conditions and have the advantage of requiring small volumes of soil and producing fast results. There are many types of heat probes commercially available, with limited—though—comparative assessment available in the literature. The current paper deals with the assessment of ground characteristics of seven samples of soil and rock collected from a certain area in the Mediterranean island of Cyprus. Such properties are the thermal conductivity, the thermal diffusivity, the volumetric heat capacity, but there are some other physical properties also. The laboratory testing was done under transient conditions and included measurements taken by two needle probes and one surface probe from two different commercial apparatuses. Comparison of the obtained results for the thermal properties of the samples was made and was also supported by numerical simulations using the COMSOL Multiphysics software through a finite element analysis method on the convection–diffusion equation for heat transfer. Laboratory testing on physical properties of the samples such as moisture content, specific gravity, permeability and particle size distribution was also performed, yielding useful results related to the assessment of the thermal properties.
Keywords: Ground thermal conductivity; Heat probe comparison; Soil thermal properties; Thermal conductivity laboratory thermal test; Thermal conductivity methodology